Characteristics and risk factors of pulmonary arterial hypertension in patients with primary Sjögren's syndrome. (6th April 2018) - Yan, Shumin; Li, Mengtao; Wang, Hui; Yang, Xiaoxi; Zhao, Jiuliang; Wang, Qian; Liu, Yongtai; Lai, Jinzhi; Tian, Zhuang; Song, Hui; Zhao, Yan; Zeng, Xiaofeng
Abstract: Aim: To describe baseline characteristics of patients with primary Sjögren's syndrome (pSS) with right heart catheterization (RHC)‐confirmed pulmonary arterial hypertension (PAH) and explore risk factors for PAH in pSS. Methods: This case–control study included consecutive patients hospitalized with pSS–PAH from 2007 to 2015, and pSS patients without PAH (in a 4 : 1 ratio) as controls. All patients fulfilled the 2002 American‐European Consensus Group classification criteria for pSS–PAH was defined according to RHC‐based European Society of Cardiology/European Respiratory Society guidelines. Associated variables were analyzed by univariate binary logistic regression to identify possible risk factors for PAH. Results: Twenty‐nine patients with RHC‐confirmed pSS‐PAH were included (mean age at onset, 38.4 ± 8.3 years; mean pSS duration, 54.6 months). PAH was the initial manifestation of pSS in 12 patients (41.4%), and shortness of breath was the most common symptom (29/29, 100%). Mean pulmonary arterial pressure was 51.8 ± 10.0 mmHg, mean cardiac index was 2.3 ± 0.8 L/min/m 2, and mean pulmonary vascular resistance was 13.0 ± 6.0 Wood units in this group. Treatments included immunosuppressive agents (93.1%) and PAH‐targeted therapies (86.2%). We identified four independent risk factors for PAH in pSS: Raynaud's phenomenon (odds ratio [OR] = 9.660, P = 0.000), rheumatoid factor ≥ 200 U/mL (OR = 6.691, P = 0.001), hepatic injury (OR = 3.284, P = 0.008) and pericardial effusion (OR = 3.279, P = 0.016). Conclusions: PAH can be the first manifestation of pSS. The pSS patients with Raynaud's phenomenon, high‐titer rheumatoid factor, hepatic injury or pericardial effusion should be screened for PAH.